2012
DOI: 10.3727/096368912x636803
|View full text |Cite
|
Sign up to set email alerts
|

Human Insulin Secreted from Insulinogenic Xenograft Restores Normoglycemia in Type 1 Diabetic Mice without Immunosuppression

Abstract: In the present study, we examined the therapeutic potential of human amnion-derived insulin-secreting cells for type 1 diabetes. Human amniotic mesenchymal stem cells (hAMs) were isolated from amnion and cultivated to differentiate into insulin-secreting cells in vitro. After culture in vitro, the differentiated cells (hAM-ISCs) were intensively stained with dithizone and secreted insulin and c-peptide in a high-glucose-dependent manner. They expressed mRNAs of pancreatic cell-related genes, including INS, PDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 45 publications
(56 reference statements)
0
24
0
1
Order By: Relevance
“…However, protein expression of human insulin, glucagon, and somatostatin was only detected in differentiated cells. The differentiated ILC also showed abundance of pancreatic transcription factors ngn3 and isl1, and were able to secrete insulin in response to glucose . Transplantation of undifferentiated hCMSC or differentiated ILC in STZ‐induced diabetic mice restored normoglycemia .…”
Section: Preclinical Applicationsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, protein expression of human insulin, glucagon, and somatostatin was only detected in differentiated cells. The differentiated ILC also showed abundance of pancreatic transcription factors ngn3 and isl1, and were able to secrete insulin in response to glucose . Transplantation of undifferentiated hCMSC or differentiated ILC in STZ‐induced diabetic mice restored normoglycemia .…”
Section: Preclinical Applicationsmentioning
confidence: 97%
“…Long‐term cultures of hCMSC have been successfully maintained while retaining their ability to differentiate into adipogenic, oesteogenic, chondrogenic, and neuronal lineages . hCMSC can also form islet‐like cell clusters (ILC) on stepwise exposure to serum‐free differentiation media.…”
Section: Preclinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that hAMSC and UC-MSC possess an immunoprivileged status as well, which is in part due to the expression of low to moderate levels of surface MHC-I, and the presence of low or even absent levels of MHC II and costimulatory molecules (e.g., CD40, CD80, CD86) [6,8,11,19,55,65,129,130,131]. …”
Section: Immunological Properties Of Hamsc and Uc-mscmentioning
confidence: 99%